CODESRIA Bulletin, No 1, 2025 - Special Issue Reflection on the Contribution of CODESRIA Second Executive Secretary - Journal System (CODESRIA Bulletin, 2025)
In this Issue Walking with Professor ABDALLA S. BUJRA // Cheminer avec le professeur ABDALLA S. BUJRA Prof. ABDALLA BUJRA, 1938–2025: CODESRIA's Towering Pillar Godwin Murunga .................................................................... 3 Prof. ABDALLA BUJRA, 1938–2025: le pilier gigantesque du CODESRIA Godwin Murunga ........................................................ 7 Editorial to Inaugural Issue of Africa Development, Volume 1, Number 1, 1976 (Republished) Abdalla S. Bujra .................11 Tributes to ABDALLA BUJRA // Hommages à ABDALLA BUJRA 4. Condoléances à la famille de BUJRA et au CODESRIA Condolences to Bujra's family, and to CODESRIA Taladidia Thiombiano .................................15 5. Professor ABDALLA SAID BUJRA, 1938–2025: A Pioneer Pan-Africa Scholar, An Institution-Builder and Man of Conscience Michael Chege ......................................................................15 6. A Tribute to ABDALLA BUJRA Peter Anyang' Nyong'o .......................................................................17 7. Homage to ABDALLA BUJRA Mahmood Mamdani. .......................................................................18 8. ABDALLA BUJRA: A Life of Unparalleled Service Adebayo Olukoshi ................................................................19 9. ABDALLA BUJRA's Legacy in Building the CODESRIA Community Mshaï Mwangola ..............................................20 10. ABDALLA S. BUJRA, and Futures Studies in Africa: A Noticer's Environmental Scanning Leopold Mureithi ............................22 Other Thematic Interventions // Autres interventions thématiques 11. Why France Can't Be Nigeria's Strategic Partner Yusuf Bangura .............................................................................................27 12. Indigenous African Knowledge and the Challenge of Epistemic Translation Zubairu Wai ................................................40 Announcements // Annonces 13. African Fellowships for Research in Indigenous and Alternative Knowledges (AFRIAK).......................................54 14. Bourses pour la recherche sur les savoirs indigènes et alternatifs en Afrique (AFRIAK)...........................................57